Hip-hop autochtone au Québec. Oralités contemporaines au gré des ondes politiques et médiatiques - Audet, Véronique (Inter : art actuel, 2009)
An article from Inter, on Érudit.
Publisher: Les Éditions Intervention

Les voix du tambour. Traditions et innovations musicales chez de jeunes Atikamekw Nehirowisiwok, Québec - Jérôme, Laurent (Jeunesses autochtones. Affirmation, innovation et résistance dans les mondes contemporains, 2009)

Tusarnituuq! Nagano In The Land Of The Inuit - Lajeunesse, Félix (Filmoption International, 2009)
In September 2008 Canada’s most prestigious orchestra, the acclaimed Orchestre symphonique de Montreal (OSM), embarked on its first ever tour of the Canadian Arctic. Lead by internationally celebrated conductor Kent Nagano, the OSM's program featured a concert of music from the classical repertoire, including Stravinksy’s Histoire du soldat narrated in Inuktitut, the language of the Inuit people, and a new work inspired by Inuit throatsinging from Canadian composer Alexina Louie. Offering viewers intimate access to Maestro Nagano, the artists, and the remote Inuit communities they visit, this stunning documentary captures an extraordinary meeting of two worlds through music.

Du teueikan au hip-hop, des harangues à l’art action - Sioui Durand, Guy (Inter : art actuel, 2009)